Effects of different fin parameters on temperature and efficiency for cooling of photovoltaic panels under natural convection - Bayrak, Fatih; Öztop, Hakan Fehmi; Selimefendigil, Fatih (Pergamon-Elsevier Science Ltd, 2019)
The photovoltaic panels are one of the most efficient energy systems that generate electricity by absorbing the solar radiation. Nevertheless, when the sun's rays are converted to electricity, a high amount of waste heat is generated. Therefore, the efficiency of photovoltaic (PV) panels needs to be studied to minimize the amount of waste heat. There is a non-linear relationship between the temperature, the current and the voltage values produced by the PV panels. In the present study, the performance of 75 W PV panels with polycrystalline cell structure under Elazig, Turkey climatic conditions were experimentally investigated. The system performances such as temperature, power and efficiencies were analyzed by applying different fin parameters (length, sequences) to PV panels. The aluminum fins were applied with 10 different configurations as given by A1-A10. The cell temperatures, output powers, power loss ratios and energy-exergy efficiencies were calculated based on measurements of the experimental study. It was observed that the temperature did not distributed homogeneously on the PV panel. In terms of the efficiency, the fins are designed as staggered array and the 7 cm x 20 cm dimensions showed the best results. The highest energy and exergy efficiencies values of the finned panels (A5) were calculated as 11.55%, and 10.91%, respectively.
Keywords: Photovoltaic; Fins; Energy; Exergy; Natural convection; Passive cooling